Orexin-1 and orexin-2 receptor antagonists reduce ethanol self-administration in high-drinking rodent models - Anderson, Rachel I.; Becker, Howard C.; Adams, Benjamin L.; Jesudason, Cynthia D.; Rorick-Kehn, Linda M. (Frontiers in Neuroscience, 2014)
To examine the role of orexin-1 and orexin-2 receptor activity on ethanol self-administration, compounds that differentially target orexin (OX) receptor subtypes were assessed in various self-administration paradigms using high-drinking rodent models. Effects of the OX1 antagonist SB334867, the OX2 antagonist LSN2424100, and the mixed OX1/2 antagonist almorexant (ACT-078573) on home cage ethanol consumption were tested in ethanol-preferring (P) rats using a 2-bottle choice procedure. In separate experiments, effects of SB334867, LSN2424100, and almorexant on operant ethanol self-administration were assessed in P rats maintained on a progressive ratio operant schedule of reinforcement. In a third series of experiments, SB334867, LSN2424100, and almorexant were administered to ethanol-preferring C57BL/6J mice to examine effects of OX receptor blockade on ethanol intake in a binge-like drinking (drinking-in-the-dark) model. In P rats with chronic home cage free-choice ethanol access, SB334867 and almorexant significantly reduced ethanol intake, but almorexant also reduced water intake, suggesting nonspecific effects on consummatory behavior. In the progressive ratio operant experiments, LSN2424100 and almorexant reduced breakpoints and ethanol consumption in P rats, whereas the almorexant inactive enantiomer and SB334867 did not significantly affect the motivation to consume ethanol. As expected, vehicle-injected mice exhibited binge-like drinking patterns in the drinking-in-the-dark model. All three OX antagonists reduced both ethanol intake and resulting blood ethanol concentrations relative to vehicle-injected controls, but SB334867 and LSN2424100 also reduced sucrose consumption in a different cohort of mice, suggesting nonspecific effects. Collectively, these results contribute to a growing body of evidence indicating that OX1 and OX2 receptor activity influences ethanol self-administration, although the effects may not be selective for ethanol consumption.